Determination Analysis Segmentation, Targeting and Positioning (STP) On The Level Sales at Upnormal Coffee in Palu - Rombe, Elimawaty; Muzakir (Economics and Business Journal (ECBIS), 2023)
This study aims to assess and analyze whether the marketing strategy STP (Segmentation, targets, and position) to the level of sales has been implemented by Upnormal Coffee Beach in Palu which has reached more than one year (2021- 2022). This type of research is quantitative descriptive. The population in this study were all employees of Upnormal Coffee while the sample of this research is all employees of Upnormal Coffee as many as 36 employees as respondents using saturation sampling, the sampling technique when all members of the population were used as a sample. The data collection techniques were performed by means of a questionnaire conducted interviews and questionnaires. Based on the results of this study with multiple linear regression analysis, regression equation Y = 8,944+ 0.164 X1 + 0.061 X2 + 0,032 X3 + e. Basedonn statistical analysis data, the indicators in this study is valid and the variables are reliable. In the classical assumption, in said that indicator otherwise normal distribution and correlation Linear in significance between each independent variable and the dependent variable, to the amount of influence Segmentation, Targeting and Positioning are all having a positive direction and not significant in their influence on the level of sales in Upnormal Coffee in the city of Palu